SOFTWARE – CENTRO DE ESTRELLA - Méndez Córdova, Jason (2019)
This investigation work was designed for the calculation of stars' center-polar axes centers of turns, studying and analyzing the movements and certain stars' behaviors. For this work you design a method of numeric analysis of I calculate of stars for a position of coordinated of n data (I center of turn), and designing for it a program seudocodigo stops then to elaborate their denominated corresponding software STAR CENTER, software that is used in field of the Observational astronomy with the use of a professional telescope Takajashi 1.30mts and 15cm of lens; cameras CCDST7, digital cameras Coolpix, cameras with movies. The designed software has the easiness of being compatible with most of files of images: jpg, bmp, gif. Their use is important to know the center of stars' turn and this way to determine its possible positions and coordinated, as well as the determination of the polar axis, the numeric analysis is based in right of adjustments, infinitesimal analysis, programming structured with a presentation of simple platform for the understanding of the same one.